Analisis Kinerja Keuangan Pemerintah Nagari Situmbuk Tahun 2018-2022 - Daffa, Muhammad; Mustika, Rasyidah; Andriani, Wiwik (Journal of Applied Accounting And Business, 2023)
This research aims to determine the financial performance of Tanah Datar Nagari Situmbuk Regency 2018-2022. The research paradigm used is descriptive qualitative. Research methods namely case studies. Data collection techniques using in-depth interviews, observation and study document. Research results The research results show that the value of the financial dependency ratio Nagari Situmbuk in 2018-2022 tends to experience an increase every year. With value The highest regional financial dependency ratio occurred in 2021, namely 99.73% and the lowest ratio value in 2020 was 99.42%. Results of efficiency ratios from 2018-2020 categorized as quite efficient, and in 2021 Nagari Situmbuk will be categorized as efficient, so This states that there will be changes from 2020 to 2021, regarding the realization of spending. The decline in the operational expenditure matching ratio amidst an increase in total operational expenditure as well as total regional expenditure in Nagari Situmbuk indicating that total expenditure other than operational expenditure in Nagari Situmbuk experienced increases and decreases. Although a percentage fee in Nagari Situmbuk is quite high. With the highest ratio of capital expenditure to total expenditure in the year 2018, namely 45.96% and the lowest ratio value in 2021 was 14.20%